EDUCATION AS SUBJECTIVATION: REFLECTIONS ON SELF CARE IN MICHEL FOUCAULT AND JOHN DEWEY - Arlan Schütz , Jenerton; Nogueira, Suelen; Leal Cordeiro, Lavinia; Barbosa Costa, Milka (CIPEEX, 2024)
THE CONCEPT OF SELF-CARE IS THEMATIZED BASED ON FOUCAULT’S HERMENEUTICS OF THE SUBJECT (2014) AND DEWEY’S DEMOCRACY AND EDUCATION (1994), IN ORDER TO FORGE SUBSIDIES CAPABLE OF ELUCIDATING THE IMPORTANCE OF SUCH A CONCEPT IN THE CONSTITUTION OF PROCESSES FORMATIONS AND THE COMMON HUMAN WORLD ITSELF. IT STARTS FROM THE PERSPECTIVE OF FOUCAULT’S NOTION OF SELF-CARE, IN ORDER TO UNDERSTAND HOW THE REPOSITIONING OF THE PROBLEM OF THE PHILOSOPHICAL PROBLEM OF KNOWING YOURSELF IS TAKEN AS SELF-CARE. FURTHERMORE, IT IS CONSIDERED THAT THE THEORIZATIONS OF JOHN DEWEY’S EDUCATIONAL PROJECT REMAIN EXTREMELY CURRENT, ESPECIALLY AT A TIME WHEN WE WITNESS THE EMPTYING OF THE FORMATIVE MEANING OF THE SUBJECT, AND THE HEAVY EMPHASIS ON DISCOURSES OF RESULTS AND PURPOSES. IN FOUCAULT, WE CAN SAY THAT THESE ARE THE TWO CHARACTERISTICS OF THE INSTRUCTIO: THE FORMATIVE AND THE CORRECTIVE ELEMENT; IN DEWEY, IT’S ABOUT LEARNING FROM EXPERIENCE, AND REORGANIZING IT, CORRECTIVELY, AS A CONTINUUM. SINCE EDUCATION IS INSTRUCTIONAL, IT HAS THE FORMATIVE AND CORRECTIVE SENSE, AND THIS ECHOES THE SENSE OF EDUCATION AS A REORGANIZATION OF EXPERIENCE AS A CARE OF THE SELF, A CARE THAT MAKES THE SUBJECT IN HIS FORMATIVE PROCESS AND EXPERIENCES CAN CONTINUOUSLY FACE LIFE, IN ADDITION TO BRINGING UP REASONS TO GOVERN HIMSELF THROUGHOUT HIS FORMATIVE PROCESS.